2014
DOI: 10.1057/biosoc.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the ‘therapeutic misconception’: Research, care and moral friction

Abstract: In research ethics regulation, health care and research are depicted as serving distinct goals, and policies are in place to prevent what is seen as patients' misconceived understanding of research as health care. On the basis of ethnographic research in four Danish hospitals in conjunction with a cardiovascular drug trial in patients with chronic disease, we argue that the objectives of health care and research often merge in mutually constitutive practices. We build on observations of trial activities, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…This is particularly so in the context of cancer genetics where many hybrid activities take place given its inherently translational dimensions (Hallowell, 2009). Highlighting how the moral framing of research and clinical care are often closely and complexly entwined, Wadman and Hoeyer (2014) point out that it is important to not see this necessarily as a dilemma or obstacle but as a way to understand how both can thrive on coexistence and the way that knowledge, work ethics and emotions emerge in tandem (p. 7; see also Timmermans, 2010). While the enmeshed boundaries between research and care in transnational research generate different questions and challenges, given inequities and disparities in resources, it is important to see how and in what ways for different groups and individuals in specifi c local contexts research is constituted as a resource and resourcefully acted upon.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly so in the context of cancer genetics where many hybrid activities take place given its inherently translational dimensions (Hallowell, 2009). Highlighting how the moral framing of research and clinical care are often closely and complexly entwined, Wadman and Hoeyer (2014) point out that it is important to not see this necessarily as a dilemma or obstacle but as a way to understand how both can thrive on coexistence and the way that knowledge, work ethics and emotions emerge in tandem (p. 7; see also Timmermans, 2010). While the enmeshed boundaries between research and care in transnational research generate different questions and challenges, given inequities and disparities in resources, it is important to see how and in what ways for different groups and individuals in specifi c local contexts research is constituted as a resource and resourcefully acted upon.…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent commentators have noted how the distinction between research and treatment in biobanking is becoming increasingly difficult to delineate (Burke et al, 2014;Wadmann and Hoeyer, 2014;Smith and Aufox, 2013;Pullman and Hodgkinson, 2006) and that this may in fact be contributing to what has been termed therapeutic misconception. Zawati and Knoppers (2012) have suggested that international norms ought to be set up to guide the return of individual research results and incidental fi ndings based on biobank research as one way of ameliorating some of these problems arising from this misconception.…”
Section: Discussionmentioning
confidence: 99%
“…This collapse in the distinction between research and treatment is giving rise to novel forms of responsibility and ambiguity to various practitioners, such as physicians, biobankers, as well as laboratory technicians (cf. Wadmann & Hoeyer, 2014). Indeed, there are increasing examples of the diffi culties that states, for example, have in trying to define the scope of responsibility between, patients, research subjects, physicians, and biobankers when it comes to managing fi ndings (Tupasela, 2015;Tupasela & Liede, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, some scholars from both bioethics and sociology fields have argued that 'taking care and caring for participants seem to be an inherent part of e even prerequisite for e scientific work' (Jespersen et al, 2013, p. 3) and that, from an epistemological point of view, 'clinical research and clinical practice are not sharply distinct but intimately intertwined' (Anderson, 2010, p. 46). Empirical social science studies have suggested that the organization of clinical trials often allows for close relationships to form, facilitating the provision of quality health care as well as other benefits appreciated by participants, including emotional support and increased time commitments of physicianinvestigators (Wadmann and Hoeyer, 2014;Timmermans and McKay, 2009). It was shown that research participants, while being aware that they are not in a healthcare setting, often report to appreciate relationships with investigators more than those with traditional healthcare providers (Easter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%